Unlocking Human Capital in the Public Sector: When Does Overqualification Improve Civil Servants' Performance? - Chao Pan; Zheng Jiang; Tingting Song (Public Administration and Development, 2026)
ABSTRACT Although overqualification among public employees is becoming increasingly prevalent, previous studies have largely overlooked its nonlinear effects. Based on Conservation of Resources Theory, this study analyzes data from 2089 civil servants and finds that: (1) A U‐shaped relationship exists between perceived overqualification and performance, with this relationship mediated by task significance. (2) Public service motivation moderates the impact of overqualification on task significance. These findings offer a nuanced perspective on overqualification, suggesting that public sector should more effectively recognize and manage varying levels of overqualification among civil servants.